+0  
 
0
30
1
avatar

t_1 (first term): p^2/2

 

r (common ratio): p/2

 

t_n (nth term): p^9/256

Guest Nov 6, 2017
Sort: 

1+0 Answers

 #1
avatar+78756 
+1

We need to solve this :

 

(p^2 / 2 ) * (p/2)^(n -1)  = p^9 / 256    where n is the nth term

 

Multiply through by  2 / p^2

 

(p / 2)^(n -1)  =  p^7 / 128

 

Note   p^7 / 128  =   p^7 / 2^7  =  ( p / 2)^7

 

So......

 

(p / 2) ^(n - 1)  =  (p /2 )^7

 

Since the bases are the same, solve for the exponents

 

n - 1  = 7      add 1 to both sides

 

n  =  8   terms

 

 

cool cool cool

CPhill  Nov 6, 2017

8 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details